Prevalence and clinico-radiological profile of chronic rhino-sinusitis in patients visiting a tertiary care hospital - Ghimire, Bibek; Prasad Koirala, Krishna; Chandra Rijal , Krishna; Gautam, Shreya; Sapkota, Sagun; Shrestha, Nischal; Thapa, Madan (Journal of Chitwan Medical College, 2025)
Introduction: Chronic rhinosinusitis (CRS) is a long-term inflammatory condition of the nasal and paranasal sinuses that significantly impairs quality of life and requires on-going management. This study aimed to evaluate the clinical and radiological profiles of CRS in patients from a tertiary care hospital in western Nepal. Method: A hospital-based descriptive cross-sectional study was conducted among all patients visiting the outpatient as well as in patient department of Otorhinolaryngology at Manipal Teaching Hospital, Pokhara Nepal from 09 Apr to 08 Dec 2024, after obtaining ethical approval. Convenience sampling was employed, and 1050 patients were screened for CRS using the Task Force Criteria. Data were collected using a structured proforma, clinical examination, and radiological evaluation. Descriptive statistics were expressed as frequencies and percentages, and association were analysed using chi-square tests, as appropriate. Result: Among the 1050 patients screened, the prevalence of chronic rhinosinusitis was 100(9.52%). Nasal blockage was the most common symptom, seen in 67(67.00%) patients, and septal deviation was noted in 74(74.00%) patients during anterior rhinoscopy. CT findings revealed anterior ethmoidal sinusitis in 95(95.00%) patients and maxillary sinusitis in 74(74.00%) patients. Anatomical variations identified on CT included septal deviation in 78(78.00%), concha bullosa in 41(41.00%), and Agger Nasi cells in 38(38.00%). A significant correlation was found between deviated nasal septum (DNS) and contralateral concha bullosa (r=0.34, p<0.01). Conclusion: CRS predominantly affects young adults, with anterior ethmoidal sinusitis being more prevalent. CT imaging revealed a high prevalence of anatomical variations. Significant correlation between DNS and contralateral concha bullosa was observed.